Techno-economic-environmental evaluation framework for integrated gas and electricity distribution networks considering impact of different storage configurations. (February 2021) - Reza Hosseini, Seyed Hamid; Allahham, Adib; Vahidinasab, Vahid; Walker, Sara Louise; Taylor, Phil
Graphical abstract: Highlights: Techno-Economic-Environmental (TEE) operation of Gas & Electricity Networks (GEN) evaluated. All the parameters affecting the TEE performance of GENs were studied. Both single-vector storage and vector-coupling storage devices were investigated. Impact of storage configuration on the TEE performance of GENs was investigated. Abstract: This paper presents an evaluation framework for Techno-Economic-Environmental (TEE) performance of the Integrated Gas and Electricity Distribution Networks (IGEDNs). The proposed framework is based on a coupled gas and electric load flow model, facilitating the consideration of all the parameters affecting the operation of IGEDNs, such as different gas mixtures, gas temperature, pipeline characteristics and the electricity network topology. This framework can assess the impact of different storage configurations, different levels of Renewable Energy Sources (RESs) and different levels of energy demand on the amount of imported energy from the upstream networks, operational costs and emissions of the IGEDNs. The evaluation framework can perform the TEE operational analysis of future scenarios of IGEDNs through various coupling components and storage devices including Single-Vector Storage (SVS) as well as Vector-Coupling Storage (VCS) devices to provide a basis for well-informed design choices for meeting the Greenhouse Gas (GHG) reduction targets. The TEE evaluation framework is tested on a real-world case study from a rural area in Scotland, and analysed from different aspects, to show the effectiveness of the model for analysis of the interactions of gas and electricity distribution networks. The results reveal that integrated operation of the gas and electricity networks improves all the considered technical, economic and environmental parameters.